Analisis Penerapan Metode Eksploratif pada Pembelajaran Seni Tari untuk Meningkatkan Kreativitas Siswa Kelas 2 di SDN Made 1 Surabaya - Ellisa Diani Pratiwi; Afib Rulyansah; Pance Mariati; Dewi Widiana (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
This study aims to analyze the application of exploratory methods in learning dance to increase the creativity of grade 2 students at SDN Made 1 Surabaya. The research method used is descriptive qualitative where this research requires data in the form of descriptive information by building a theory based on the data obtained. Sources of data used in this study are primary and secondary data sources. The techniques used in collecting data are observation, interviews, and documentation. The target audience for this study were grade 2 teachers, grade 2 students and the principal of SDN Made 1 Surabaya. The exploratory method applied by the teacher goes through the stages of planning, providing initial material, the exploration process, improvisation, and evaluation. The results obtained are that grade 2 students at SDN Made 1 Surabaya are able to develop imagination, increase creativity, and improve student learning outcomes through exploratory learning.